An assessment of states' government Websites in Malaysia - Mohammed Yasin, Nazreena; Mohd Adnan, Normala; Omar, Muhamad Fuzi; Hossain, Ishtiaq; Mokhtar, Tunku Mohar; Jamaiuddin, Norhaslinda; Abdul Hamid, Rohana (2017)
A study on this area is undoubtedly important to ascertain the level of progress achieved by each state website. Furthermore, no such study has been carried out by accessing all the states websites based on the online presence in the context of Malaysia. Hence, this study could inform the state governments on the progress deemed by their websites and implementation alone without proper maintenance is insufficient. Progress and changes towards the betterment of the system is highly needed.